Uprooted but Unbroken: Exploring the Experiences of Yemeni Students at Yemeni Schools in Cairo - Abdulhadi, Sumood (AUC Knowledge Fountain, 2024)
To contribute towards filling the research gap on the experiences of uprooted Yemeni children in Egypt, this phenomenological research was designed to explore the experiences of uprooted Yemeni students in Egypt. Twenty male and female Yemeni students from four Yemeni schools in Cairo participated in semi-structured interviews. The findings revealed that these uprooted children face various economic, social, and academic challenges within the Yemeni schools in Cairo, which seem to hinder their educational progress. Moreover, Yemeni children face difficulties not only within the Yemeni schools in Cairo but also in the streets and Egyptian schools of Cairo. Nevertheless, they appeared to display resilience, as evidenced by positive self-concept, effective coping strategies, academic engagement, and cultural identity. The research offers recommendations to stakeholders, including school principals, teachers, policymakers, governments, and organizations, urging them to implement interventions that foster an inclusive and supportive learning environment for uprooted Yemeni children that ensuring their education and well-being. Keywords: displaced, refugee, children, students, schools, education, experience, challenge, war, Yemen.